2020
DOI: 10.18825/iremjournal.536247
|View full text |Cite
|
Sign up to set email alerts
|

Açik Ve Uzaktan Eği̇ti̇mi̇n Kadin Güçlendi̇rmesi̇nde Önemi̇: Anadolu Üni̇versi̇tesi̇ Örneği̇

Abstract: Küreselleşen dünyada toplumun sosyal refah seviyesinin yüksekliği bireylerinin mutlu olmasına bağlı olduğuna göre eğitimin bu anlamdaki rolü çok önemlidir. Çalışmada, güçlendirme kavramı ve boyutları ile kadın güçlendirmesi kavramı teorik ve ampirik olarak incelenmiştir. Literatürde kadın güçlendirmesi ile eğitim arasındaki ilişkiyi sorgulayan araştırmalar irdelenerek, açık ve uzaktan eğitim sisteminde öncü olan Anadolu Üniversitesi Açıköğretim Sistemi'nden (AÖS) bahsedilmiştir. Daha sonra AÖS'ten eğitim alanl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 7 publications
0
1
0
Order By: Relevance
“…Azaiza (2012) carried out research on 150 female students studying at the Palestine Open University and concluded that distance education is potential solutions that will help women reach their educational goals. The results of the study of Günsoy et al (2019) showed that Anadolu University Open and Distance Education System in Turkey has the positive effects on social and economic empowerment and women's participation on private decisions, economic trust, private independence and freedom, individual mobility.…”
Section: Introductionmentioning
confidence: 99%
“…Azaiza (2012) carried out research on 150 female students studying at the Palestine Open University and concluded that distance education is potential solutions that will help women reach their educational goals. The results of the study of Günsoy et al (2019) showed that Anadolu University Open and Distance Education System in Turkey has the positive effects on social and economic empowerment and women's participation on private decisions, economic trust, private independence and freedom, individual mobility.…”
Section: Introductionmentioning
confidence: 99%